A method on acrylamide elimination: Comparing and tracing reaction pathways of acrylamide and catechin (catechin quinone) using UHPLC-Q-exactive orbitrap mass spectrometry. (1st June 2023) - Liu, Xinyu; Su, Jingjing; Geng, Yaqian; Chen, Fang; Huang, Baoyong; Yang, Hongju; Ma, Xiao; Hu, Xiaosong; Ji, Junfu; Ma, Lingjun
Highlights: Acrylamide prefers having nucleophilic addition with quinones. Acrylamide is prone to react with catechin's B ring via a redox reaction than its A ring via electrophilic addition. Thirteen reaction products were detected by UHPLC-Q-Exactive Orbitrap Mass Spectrometry. Abstract: Acrylamide (AA) elimination is significant in thermal-processing foods that rich in carbohydrate and asparagine. Here, catechin (CAT) and its quinone were utilized to investigate and evaluate the reaction rate of AA's characteristics (electrophilicity, oxidizing ability, and nucleophilicity) and trace the reaction pathways to eliminate AA in model system at 25 °C and 150 °C. It is revealed that AA prefers nucleophilic additions with quinone (kAA-CATQ = 1.1E-2 min −1 > kAA-CAT = 3.1E-3 min −1 ). It is prone to react with the B ring of CAT (kAA-4MC = 1.4E-3 min −1 ) via the redox reaction, rather than the A ring (kAA-PHL = 1.0E-4 min −1 ) through the electrophilic reaction. For the investigation of unknown products resulting from the above reactions, a process incorporating mechanism and tentative product speculation was implemented. Thirteen products were partially detected based on the extracted ion chromatography and MS spectrum from UHPLC-Q-Exactive Orbitrap Mass Spectrometry. These results provide a new perspective to eliminate AA in thermal-processing foods.